2016
DOI: 10.1186/s12939-016-0360-6
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of unemployment in Europe (2008–2011): a longitudinal analysis of income and financial strain as mediating factors

Abstract: BackgroundUnemployment has a number of negative consequences, such as decreased income and poor self-rated health. However, the relationships between unemployment, income, and health are not fully understood. Longitudinal studies have investigated the health effect of unemployment and income separately, but the mediating role of income remains to be scrutinized. Using longitudinal data and methods, this paper investigates whether the effect of unemployment on self-rated health (SRH) is mediated by income, fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…While Huijts et al (2015) use a cross-sectional design with control for observed differences at baseline, Tøge (2016) uses a longitudinal design that controls for all time-invariant factors, including the unobserved. This implies that the effect presented by Huijts et al (2015) could be overestimated (due to selection bias), while the effect presented by Tøge (2016) is on the conservative side. However, both studies suggest that employment positively affects health through mechanisms other than income alone; for instance, through supporting agency and self-efficacy, stimulating a more regular and healthy lifestyle and providing social contacts (Mirowsky & Ross, 2003).…”
Section: Employmentmentioning
confidence: 97%
See 2 more Smart Citations
“…While Huijts et al (2015) use a cross-sectional design with control for observed differences at baseline, Tøge (2016) uses a longitudinal design that controls for all time-invariant factors, including the unobserved. This implies that the effect presented by Huijts et al (2015) could be overestimated (due to selection bias), while the effect presented by Tøge (2016) is on the conservative side. However, both studies suggest that employment positively affects health through mechanisms other than income alone; for instance, through supporting agency and self-efficacy, stimulating a more regular and healthy lifestyle and providing social contacts (Mirowsky & Ross, 2003).…”
Section: Employmentmentioning
confidence: 97%
“…As employment is a major source of income for households, health is assumed to be positively affected by employment by reducing poverty risks (Bartley, 1994;Catalano, 1991;Catalano et al, 2011;Tøge, 2016), though this mediating effect of income is somewhat disputed (Huijts et al, 2015;Tøge, 2016). Using the exact same longitudinal data (EU-SILC), Huijts et al (2015) and Tøge (2016) come to different conclusions when investigating the health effects of unemployment.…”
Section: Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between unemployment and poor health at the individual level has been demonstrated in many studies (e.g. Schaller and Stevens ; Tøge ), although the causal direction has been disputed (e.g. Schmitz ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Namely, unemployment status imposes to individuals and their families additional burden as non-pecuniary costs since employment is not only a source of income, but also provides social relationships, identity in the society and individual self-esteem (Winkelmann and Winkelmann 1998;Tøge 2016). The empirical literature shows that unemployed persons manifest significant symptoms of deteriorated health conditions such as higher incidence of stress, anxiety and depression (Bordea and Pellegrini 2014).…”
Section: Literature Reviewmentioning
confidence: 99%